Comparison of ZnO interlayers in inverted bulk heterojunction solar cells - Bekci, D. Rana; Karsli, Adem; Cakir, A. Cagatay; Sarica, Hizir; Guloglu, Alper; Gunes, Serap; Erten-Ela, Sule (ELSEVIER SCI LTD, 2012)
This paper is devoted to the development of inverted-type bulk heterojunction solar cells based on zinc oxide (ZnO) interlayers, poly-3-hexylthiophene (P3HT) and PCBM using simple synthesis procedures and deposition techniques. We compare device structures and performances consisting of poly-3-hexylthiophene (P3HT) polymer and PCBM in contact with three different types of ZnO interlayers: a ZnO backing interlayer alone using spin coating process: nanorod ZnO interlayers from Zn2+:HO- solutions using deep coating process and finally nanorod ZnO interlayers from Zn2+:HO- solutions onto ZnO backing interlayer using spin coating process. The best device configuration is fabricated in a ZnO backing interlayer/nanorod ZnO interlayer by spincoating process/P3HT:PCBM/Gold cell architecture which exhibits a power conversion efficiency of 2.73% under 100 mW/cm(2) AM 1.5 G simulated solar emission. Atomic force microscopy (AFM) and photovoltaic device measurements are used to study the morphology and device performance of the three different types of ZnO interlayers. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Inverted-type bulk heterojunction solar cells; ZnO interlayers; Energy efficiency; PERFORMANCE; SEPARATION; LAYER; Energy & Fuels; Engineering